2021
DOI: 10.3389/fnut.2021.782270
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Vitamin D Levels and Risk of Vitiligo: Evidence From Meta-Analysis and Two-Sample Mendelian Randomization

Abstract: Background: The association between circulating vitamin D levels and risk of vitiligo was inconsistent among observational studies, and whether these observed associations were causal remained unclear. Therefore, we aimed to evaluate the effect of vitamin D on the risk of vitiigo using meta-analysis and Mendelian randomization (MR).Methods: At the meta-analysis stage, literature search was performed in PubMed and Web of Science to identify eligible observational studies examining the association of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We found no significant causal effect of blood 25(OH)D 3 or C3-epi-25(OH)D 3 on the risk of atopic dermatitis but suggest that developing atopic dermatitis raised blood 25(OH)D 3 levels. Previous MR identified no causal effects of circulating 25(OH)D or 25(OH)D 3 on the risk of vitiligo [26]. We achieved similar results, suggesting no causal effects of 25(OH)D, 25(OH)D 3 , or C3-epi-25(OH)D 3 on vitiligo.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found no significant causal effect of blood 25(OH)D 3 or C3-epi-25(OH)D 3 on the risk of atopic dermatitis but suggest that developing atopic dermatitis raised blood 25(OH)D 3 levels. Previous MR identified no causal effects of circulating 25(OH)D or 25(OH)D 3 on the risk of vitiligo [26]. We achieved similar results, suggesting no causal effects of 25(OH)D, 25(OH)D 3 , or C3-epi-25(OH)D 3 on vitiligo.…”
Section: Discussionsupporting
confidence: 86%
“…Recent genome-wide association studies (GWASs) have identified tens of thousands of genetic variants robustly associated with human complex diseases and traits [24], which as a result provide a wealth of potential IVs and facilitate MR analysis. MR analyses have investigated the causal effects of circulating 25(OH)D levels on the risk of psoriasis, atopic dermatitis, and vitiligo, suggesting that blood 25(OH)D levels confer a significant causal effect on psoriasis but not on atopic dermatitis or vitiligo [25][26][27]. Alternatively, MR suggests that genetically predicted risk of atopic dermatitis increases blood 25(OH)D level [28].…”
Section: Introductionmentioning
confidence: 99%
“…The study investigated vitiligo cases (131) and controls (207,482), which included over 16 million genetic variants. Detailed information on the study has been described in the previous study ( 20 ). The study was conducted with the signed informed consent of every participant, and each regional institutional review board oversaw it.…”
Section: Methodsmentioning
confidence: 99%
“…This disorder impresses the epidermal melanocytes and neural crest-derived melanocytes and spreads to different parts of the body such as the hair follicles and eyes. 2 Various mechanisms of melanocyte degeneration in vitiligo have been proposed. According to one theory, nerve endings in the skin release a toxic substance that can degenerate melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder impresses the epidermal melanocytes and neural crest-derived melanocytes and spreads to different parts of the body such as the hair follicles and eyes. 2…”
Section: Introductionmentioning
confidence: 99%